2015
DOI: 10.1038/nm.3788
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase 1 and 2 mutations induce BCL-2 dependence in acute myeloid leukemia

Abstract: Mutant isocitrate dehydrogenase (IDH) 1 and 2 proteins alter the epigenetic landscape in acute myeloid leukemia (AML) cells through production of the oncometabolite (R)-2-hydroxyglutarate (2-HG). Here we performed a large-scale RNA interference (RNAi) screen to identify genes that are synthetic lethal to the IDH1R132H mutation in AML and identified the anti-apoptotic gene BCL-2. IDH1- and IDH2-mutant primary human AML cells were more sensitive than IDH1/2 wild-type cells to ABT-199, a highly specific BCL-2 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
401
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(440 citation statements)
references
References 63 publications
32
401
2
5
Order By: Relevance
“…Chan et al previously demonstrated that IDH1/2 mutations can sensitize leukemic cells to venetoclax 4. However, of the 10 IDH1/2 ‐mutated AML samples assessed in this trial, 7 had co‐occurring spliceosome mutations, making it difficult to determine whether only one or both of these mutations together predict for venetoclax sensitivity.…”
Section: Figurementioning
confidence: 87%
“…Chan et al previously demonstrated that IDH1/2 mutations can sensitize leukemic cells to venetoclax 4. However, of the 10 IDH1/2 ‐mutated AML samples assessed in this trial, 7 had co‐occurring spliceosome mutations, making it difficult to determine whether only one or both of these mutations together predict for venetoclax sensitivity.…”
Section: Figurementioning
confidence: 87%
“…In vivo, IDH1-R132-KI embryos show heightened HIF1α in the brain but no changes in the hematopoietic system [28,31], suggesting that effects of d2HG on HIF1α are likely cell context-dependent. Lastly, in AML cell lines overexpressing IDH1-R132H, d2HG inhibited Cox IV and mitochondrial respiration in a manner dependent on Bcl2 [32].…”
Section: Mutation Of Idh1/2mentioning
confidence: 91%
“…The overall response rate was 15%, with another 19% of patients having reductions of blasts [156]. Responses appeared to be more frequent among patients with IDH mutation, a clinical observation that confirms preclinical studies suggesting BCL-2 to be a "synthetic lethal" partner of IDH2 mutated AML [157]. The combination of venetoclax plus decitabine/azacitidine given to patients ( 65 years) with treatment-na€ ıve AML resulted in responses in 16 of 19 evaluable patients (84%; 5 CR 1 9 CRi 1 2 PR) [158].…”
Section: Venetoclax (Abt-199)mentioning
confidence: 82%